Penokohan Series Alrawabi School for Girls Karya Tima Shomali Tinjauan Intrinsik - Fikriyah Nadia Alkatiri; Ilham Ramadhan; Haeriyyah (Jurnal Sarjana Ilmu Budaya, 2023)
ABSTRACTCHARACTERIZATION OF ALRAWABI SCHOOL FOR GIRLS SERIES BY TIMA SHOMALI (INTRINSIC REVIEW)Fikriyah Nadia Alkatiri "Characterization of Alrawabi School for Girls Series by Tima Shomali (Intrinsic Review)". Supervised by Haeriyyah, S.Ag., M.Pd.I and Ilham Ramadhan, S.S., M.A.This research is motivated by the problems that occur in the Alrawabi School for Girls series. The main problem in this series is the change in character due to bullying and revenge contained in the Alrawabi School for Girls series. The aims of this study were: to identify the character dimensions in the Alrawabi School for Girls series using Hussein Qabbani's theory, and to analyze the character painting techniques in the Alrawabi School for Girls series.The type of research used is library research, namely descriptive qualitative. The data in this study are in the form of scenes and dialogues in the series "Alrawabi School for Girls" by Tima Shomali and Shirin Kamal. The data source for this research is the series â€œAlrawabi School for Girlsâ€ by Tima Shomali. Data collection techniques using recording techniques. Methods and techniques of data analysis are (1) display, (2) reduction, and (3) drawing conclusions.The results of the study show that (1) In the Alrawabi School for Girls Series there were several characters including Maryam, Dina, Noaf, Layan, Rania, dan Ruqayya, the six characters had different character dimensions, while the character dimensions were the outer dimension, the inner dimension and the social dimension. (2) The character painting techniques used are dramatic techniques, namely speech techniques, behavior techniques, thoughts and feelings techniques, other character reaction techniques, physical painting techniques, and background painting techniques.Keywords: Alrawabi School for Girls, Character Dimension, Character Painting Techniques.